Ace of aces the life of captain Eddie Rickenbacker - Jeffers, Harry Paul 1934- (Ballantine Books, 2003)
"In this important new biography, acclaimed historian H. Paul Jeffers brings to vivid life one of the most daring and dramatic figures of twentieth-century America - Medal of Honor recipient Capt. Eddie Rickenbacker. Born to immigrant parents with humble means at the turn of the century, Edward Rickenbacker was destined to embody the ingenuity, innovation, and courage that would make the United States a world power." "Rickenbacker burst onto the national scene as one of the nation's first star race car drivers. In an era when tracks were rough and safety precautions virtually unknown, Rickenbacker pushed the fastest machines at terrifying speeds. Later in life, he would own the Indianapolis Speedway and help establish the sport of modern race car driving as we know it." "But Rickenbacker's lasting fame came as an "Ace of Aces" in World War I, a fearless fighter pilot who would chase the "Flying Circus" of the legendary Red Baron above the battlefields of France. With his "Hat-in-the-Ring" squadron, Eddie was among the first to understand that the new technology of aviation would forever change the face of warfare. Shooting down twenty-six enemy planes in just seven months, he captured the hearts of a nation back home involved in its first Great War." "Even after the war, he remained a national figure as one of the founders of Eastern Airlines. Turning his wartime experience to peacetime industry, Rickenbacker again led American interests in reshaping the world. And in one of the most dramatic chapters of World War II, a plane on which Rickenbacker flew as a civilian crash-landed in the Pacific Ocean. He survived as a castaway for twenty-four days before a rescue that defied the odds."--BOOK JACKET.